PENGARUH PROMOSI DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN DI MATAHARI DEPARTMENT STORE MEDAN MALL - SARI PEBRINA; TOGU HARLEN LBN. RAJA; ARISMAN PARHUSIP (JURNAL ILMIAH KOHESI, 2021)
This research was conducted to: (1) Knowing the promotion of products at PT Matahari Department Store Medan Mall, (2)Knowing the price of products at PT Matahari Department Store Medan Mall, (3) Knowing together (simultaneous)promotions and prices against purchasing decisions at PT. Matahari Department Store Medan Mall. This research is adescriptive quantitative method that uses numbers, ranging from data collection, interpretation of the data and theappearance of the results. The population in this study was the customers of PT Matahari Department Store Medan Mallduring the research. The sample size of the study taken by 80 people was determined by the sample technique used in thisstudy, namely random sampling (simple random sample) sampling technique is named so because in sampling, researchers"mix" subjects in the population so that all subjects are considered the same and the data is collected using questionnaireswith a likert scale that has 5 alternative answers. The results of this study show that: (1) Promotions have a positive andsignificant influence on purchasing decisions on PT. Matahari Department Store Medan Mall by 44.1%. (2) The price willhave a positive and significant influence on the purchase decision of PT Matahari Department Store Medan Mall by 61.1%.(3) There is a positive influence between promotion and price on the purchase decision at PT Matahari Departemen StoreMedan Mall with a coefficient of determination (R2) of 0.705. This means that 70.5% of its purchase decisions at PT MatahariDepartmen Store Medan Mall are affected by promotions and prices, while another 29.5 are determined by other variablesnot studied in this study.